The Society for Vascular Surgery clinical practice guidelines on the management of visceral aneurysms - Chaer, Rabih A.; Abularrage, Christopher J.; Coleman, Dawn M.; Eslami, Mohammad H.; Kashyap, Vikram S.; Rockman, Caron; Murad, M. Hassan (Journal of vascular surgery, 2020)
These Society for Vascular Surgery Clinical Practice Guidelines describe the care of patients with aneurysms of the visceral arteries. They include evidence-based size thresholds for repair of aneurysms of the renal arteries, splenic artery, celiac artery, and hepatic artery, among others. Specific open surgical and endovascular repair strategies are also discussed. They also describe specific circumstances in which aneurysms may be repaired at smaller sizes than these size thresholds, including in women of childbearing age and false aneurysms. These Guidelines offer important recommendations for the care of patients with aneurysms of the visceral arteries and long-awaited guidance for clinicians who treat these patients. [Display omitted]